Relationship of social characteristics and local economic development (LED) activity for slum upgrading in Batik Thematic Village Semarang City - Astrini Dewi Ulamdhani; Sunarti Sunarti (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2021)
The process of LED activities that starts from access to raw material, production, and product marketing will have an impact on the quality of settlements. The aspects of slum handling  affected by LED activities include: 1) street, 2) waste, and 3) garbage. The LED activities in this research are focused on 1) the business length and 2) income. The two variables of LED activity and slum handling will be assessed for correlation with social characteristics including: 1) gender, 2) education, 3) length of stay, and 4) family income. Research location is in Batik Thematic Village, Semarang City. The problems at the location in the form of environmental impacts due to the LED activities have not been supported by the involvement of LED actors. The non-optimal participation of LED actors can be seen from the lack of communal WWTP and waste banks. The purpose of this study is to examine the relationship of social characteristics and LED activities for slum upgrading. The study employed a quantitative approach, through a questionnaire technique with a population of 33 respondents. The data was processed through descriptive analysis. The results of the study illustrate that the longer the perpetrators stay,the longer the businesses start and the income get.  Meanwhile, based on gender and education level, there are no relations that affect LED activities. The social characteristics and slum upgrading has strong correlation with the aspects of the street. The aspect of waste has very weak correlation, while the garbage aspect has no relation. Street aspect has high correlation because business actors get benefit from LED product access. The waste aspect has weak correlation because there are few entrepreneurs do the process independently, while the garbage aspect does not exist due to the similarity of handling and retribution.